2001
DOI: 10.1177/146442070121500204
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vibratory stress on the welding microstructure and residual stress distribution

Abstract: Previous studies have suggested that weld microstructure may be modi ed by the presence of static stresses. In this investigation, vibratory stress was applied to mild steel specimens while they were being welded to observe its effect on the residual stress, microstructure and hardness of the material. Residual stresses were found to decrease in response to vibration whether it was applied during welding or after welding. It was found that the applied stress in uenced the grain growth process in the weld. As a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Whether vibration is induced during welding or post-welding (as in the case of VSR), the stress relief is not a direct result of the LVE, but rather a byproduct of the structural response that yields plastic deformations around the weld areas, thus achieving stress relief. This has been supported by References [9,10,11,12,13,14] and few cycles are enough, as demonstrated in References [11,15,16] and the experimental setups for GVE [10,14,15]. In the case of simultaneous vibration and welding, the weld area is further heated, which causes the yield strength to drop significantly, implying that under the same strain magnitude, the material will be more prone to plastic deformation.…”
Section: Discussionmentioning
confidence: 67%
“…Whether vibration is induced during welding or post-welding (as in the case of VSR), the stress relief is not a direct result of the LVE, but rather a byproduct of the structural response that yields plastic deformations around the weld areas, thus achieving stress relief. This has been supported by References [9,10,11,12,13,14] and few cycles are enough, as demonstrated in References [11,15,16] and the experimental setups for GVE [10,14,15]. In the case of simultaneous vibration and welding, the weld area is further heated, which causes the yield strength to drop significantly, implying that under the same strain magnitude, the material will be more prone to plastic deformation.…”
Section: Discussionmentioning
confidence: 67%
“…4 Munsi et al applied vibratory stress on low carbon steel workpieces during welding and observed that if vibration is applied during or after welding, residual stresses get reduced. 5 They also reported that the grain growth process in the weld is also influenced by this applied vibratory stress. Gu¨lenc¸et al 6 investigated the effect of welding current and shielding gas (Ar mixed with different proportion of H 2 ) on tensile strength, toughness and microstructure of AISI 304 welded joints.…”
Section: Introductionmentioning
confidence: 93%
“…When vibration was applied to cold rolled mild steel specimens during MIG welding, it resulted in grain refinement, reduction in residual stress and increase in hardness. 29 The frequency of vibration was maintained at 25 Hz during vibratory welding. Heat input, welding speed and time of vibration were also kept constant, and amplitude was varied.…”
Section: Effect On Mechanical Propertiesmentioning
confidence: 99%